Efecto de un recubrimiento a base de cedrón (Aloysia citrodora) y maracuyá (Passiflora edulis) sobre la vida útil de filetes de tilapia (Oreochromis niloticus) en refrigeración. - Shagñay Flores, Wilmer Paúl (2022)
Fish is a highly perishable product, with a shelf life of 5 days in refrigeration at a temperature of 4°C; its degradation is produced by the action of microorganisms and enzymatic reactions. This research aimed to evaluate the effect of a coating based on lemon beebrush (Aloysia citrodora) and passion fruit (Passiflora edulis) on the shelf life of tilapia (Oreochromis niloticus) fillets under refrigeration. A completely randomized block design (DBCA) was proposed in order (A*B); factor A corresponds to the concentrations of raw material A1 (70% lemon verbena concentrate, 30% passion fruit pulp), A2 (50% lemon verbena concentrate, 50% passion fruit pulp), A3 (30% lemon beebrush concentrate, 70% passion fruit pulp) and factor B corresponding to the types of gelling agents B1 (alginate), B2 (genetine) when combining factor A with factor B has obtained a total of 6 treatments. To determine the best treatment, a survey was applied to 20 people, the organoleptic attributes (aroma, appearance, flavor, and texture) were evaluated; according to the data obtained, an Anova analysis was developed to know the best treatment, it was indicated that the fourth treatment was the most accepted by the respondents with a formulation (50% lemon beebrush concentrate, 50% passion fruit pulp, 8% gelatin, and 1% hemp seed oil) with which the analyzes were carried out to the best treatment (t4) and the control (t0). When carrying out the organoleptic analysis during the 10 days in refrigeration at 4°C to the best treatment, the appearance attribute resulted in a score of 3.5, in the aroma 3.4, and in the texture 3.4. On the part of the control in appearance, it acquired a rating of 2.4, aroma 2.5, and texture 2.7. In the physicochemical analyzes of the best treatment after the 10 days of refrigeration, there was a loss of 9.3% concerning weight, a value of 5.8 for the pH, 22.9% humidity, 9.45% ash, and 1.01% titratable acidity. On the part of the control, a loss of 9.3% of the weight was determined, with a value of 5.4 on the part of the pH, 18.9% humidity, 9.45% ash, and 1.04% titratable acidity. Subsequently, the microbiological analyzes were carried out, evaluating the best treatment during the 10 days in refrigeration at 4°C, where a value of 3.4 * 105 was obtained in the total mesophiles, 10 CFU / g in Escherichia coli, and 10 CFU /g Staphylococcus aureus determining that the tilapia fillet with the best treatment extended its shelf life up to 10 days under refrigeration. Finally, the retail price was calculated, resulting in each 100g fillet with the best food coating treatment cost of 0,80 USD.